Bibliometric Study: Research Trends in Field of Archives in Jurnal Kearsipan ANRI 2015-2023 - Novelawaty, Yeni Dwi; Lawanda, Ike Iswary (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2024)
This study aims to find out how research trends in archival field. This research describes the development of the number of articles, author productivity, contribution of author institution, and a map of research development in the archival science based on keywords and author collaboration patterns in the Jurnal Kearsipan ANRI 2015-2023. The method used in this research is descriptive quantitative by conducting a search using Harzing PoP software on the Google Scholar database by writing the keyword